Implementing 3D Pageflip Teaching Materials with Coffee Diplomacy Infographics for BIPA Instructors in Hamburg - Zulaeha, Ida; Suratno, Suratno; Hasanudin, Cahyo; Supriyono, Areni Yulitawati; Juwanda, Juwanda; Afifah, Ning Imas Ati Zuhrotul Afifah (Journal of Community Empowerment, 2024)
The BIPA teaching program in Hamburg can leverage cutting-edge technology. The main focus of this program is the transformation of teaching materials presented in 3D Pageflip, featuring creative coffee diplomacy infographics integrated with technology. The involvement of BIPA instructors as change agents in this program aims to have a positive impact on the process of teaching Indonesian to Foreign Speakers in Hamburg. Additionally, this program strengthens instructors' skills in integrating technology into teaching. Advanced training and community forums will serve as platforms to enhance collaboration and exchange experiences among BIPA instructors. This partnership program continuously develops innovative learning experiences and offers a teaching model that can be adopted by other international BIPA teaching communities. The development of BIPA teaching materials presented in 3D Pageflip with coffee diplomacy infographics becomes more engaging, effective, and aligned with current trends and issues, making coffee a diplomatic infographic. BIPA instructors need support to present interesting issues to BIPA learners. This partnership program is not only about improving teaching quality but also about inviting instructors and learners to explore the potential of technology in enhancing learning at the international level as soft diplomacy.